(untitled) (Fiep Bulletin - online, 2016)
The objective of this research is to measure cardiac output and metabolic risk for people with visual impairments in the city of Temuco (DVT). The research provides a non-experimental, descriptive, cross-sectional design with a quantitative approach. The sample included 20 DVT, all male (age 42.4 ± 14.5 years). The results indicate favorable values ??for DVT cardiac response (111.8 ppm) and metabolic risk. In conclusion, DVT reveal adaptation to aerobic training beneficial scenario that could present a more oxygen and better use of it, improving cardiovascular and respiratory capacity.